Training on the Design of an Automatic Faucet Water System Using Arduino for Youth in Giri Mekar Village - Hasbullah Hasbullah; Wawan Purnama; Neris Pery Ardiansyah; Jaja Kustija; Resa Pramudita (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2022)
Nowadays, water faucets play an important role in controlling water flow. Besides that, faucets are generally moved manually by every human activity by turning or moving the faucet up or down. This manual faucet system has weaknesses, namely water wastage and easily damaged faucets. The use of automatic faucets in public facilities can minimize waste their use because generally people often forget to close the faucet again. Besides, using Arduino-based automatic water faucets can reduce the transmission of Covid 19 for the community, especially during the current pandemic. This activity aims to design Arduino-based automatic water faucets at public facilities to reduce the spread and transmission of COVID-19, especially in the Girimekar Village area, Bandung Regency. The target of this activity is youth and cadets in the area. The implementation of the Arduino-Based Automatic Water Faucet design in training resulted in a prototype unit of Arduino-based automatic water faucet using the ultrasonic sensor HC-SR04 as detection and use of an electric solenoid valve as a form of direct water control.